Temperature Adaptability Analysis of Closed Cycle Using CO2-Based Mixed Working Fluid for Underwater Platforms - Jiaqi FENG; Junpeng WANG; Zhentao CHEN; Zhengyuan LUO; Bofeng BAI (水下无人系统学报)
The supercritical CO2 Brayton cycle system is an important development direction of underwater platform power technology. However, due to the low temperature in the deep sea which is far away from the critical temperature of CO2, the cycle system has temperature adaptability problems. This paper proposed the plan to use CO2-based mixed working fluid to improve cycle temperature adaptability and further optimize cycle performance. A simple recuperative closed cycle thermodynamic model was established, and the changes in critical parameters of CO2-based mixed working fluid with the type and mass fraction of added gas were analyzed. The influence of the compressor inlet state parameters on the thermodynamic properties of the closed cycle of CO2-based mixed working fluid was clarified. Besides, the influence of the pseudo-critical point position of the mixed working fluid on the pinch point and thermal inertia of the regenerator was discussed. The results show that the mixed working fluid cycle with low critical parameters can further expand the cycle temperature range and pressure ratio to improve the cycle thermodynamic performance. However, only expanding the temperature range and reducing the pressure ratio may have an adverse impact on it. Comprehensive consideration of cycle thermal efficiency, specific power, and pinch point and thermal inertia of regenerator, the maximum thermal efficiency of CO2 + Xe(CO2/Xe: 0.5/0.5)- transcritical Rankine cycle, CO2 + SF6(CO2/SF6: 0.9/0.1)-transcritical liquid Brayton cycle, CO2 + SF6(CO2/SF6: 0.5/0.5)-transcritical Rankine cycle can be increased by 3.79% than that of the supercritical CO2 Breton cycle, and the maximum specific power can be increased by 31.6%. The pinch point of the regenerator is located at the cold end, which does not increase its thermal inertia and does not slow down the system response speed.